Menjadi Guru Pembelajaran Di Era Revolusi Industri 4.0 - Riadi, Akhmad (AZKIYA, 2021)
In Indonesia's education, globalization has had the effect of changing the way teachers teach, which used to be traditional paper-based, to now be based on information and communication technology (ICT). The functions of ICT for teachers include, first, ICT can be used to assist administrative work (Word processor & Basic Requirements, Spreadsheet). Second, ICT can be used to help package teaching materials (Multimedia). Third, ICT can be used to assist the learning management process. Fourth, ICT can be used for technical support and increase knowledge in order to realize self-running creation (antivirus, tools, network, internet, and others). Several types of ICT-based learning resources and media that can be used by teachers in elementary schools include computers or laptops, LCD (Liquid Crystal Display), Smart Television, Internet networks, E-mail (electronic mail), Power Point presentations, learning CDs. , and smart phones. To improve the ability to utilize ICT, teachers need to continue to train and familiarize their learning based on ICT as often as possible, in addition, teachers need to attend trainings to increase their knowledge in this ICT field.